miR-130a and miR-27b Enhance Osteogenesis in Human Bone Marrow Mesenchymal Stem Cells via Specific Down-Regulation of Peroxisome Proliferator-Activated Receptor γ - Seenprachawong, Kanokwan; Tawornsawutruk, Tulyapruek; Nantasenamat, Chanin; Nuchnoi, Pornlada; Hongeng, Suradej; Supokawej, Aungkura (Frontiers in Genetics, 2018)
Mesenchymal stem cell (MSC) is a type of stem cell that is capable of differentiating into osteoblasts and adipocytes. The pathological perturbation of mesenchymal stem cell fate determination is well demonstrated by the replacement of bone tissues with fat in those with osteoporosis and osteopenia. Cell fate determination can be regulated by epigenetic and post-transcriptional mechanisms. MicroRNAs (miRNAs) are small endogenous noncoding RNA molecules that mediates the post-transcriptional regulation of genes expression. We hypothesized that miRNA specified to PPARγ, a major transcription factor of adipogenesis, is responsible for the differentiation of mesenchymal stem cells into osteoblasts. Candidate miRNA that is responsible for target gene inhibition was identified from the miRNA database via bioinformatic analyses. In this study, miR-130a and miR-27b were selected for investigation on their role in specifically binding to peroxisome proliferator-activated receptor γ (PPARγ) via in vitro osteogenesis of human MSCs. During osteogenic differentiation of human MSCs, the expression level of miR-130a and miR-27b were found to be upregulated. In the meanwhile, adipogenic marker genes (PPARγ, C/EBPβ) were found to decrease, which is in contrary to the increased expression of osteogenic marker genes (RUNX2, Osterix). MSCs were transfected with mimics and inhibitors of miR-130a and miR-27b during in vitro osteogenesis followed by evaluation for the presence of osteogenic markers via quantitative gene expression, Western blot analysis and alkaline phosphatase activity assay. The overexpression of miR-130a and miR-27b is shown to enhance osteogenesis by increasing the gene expression of RUNX2 and Osterix, the protein expression of RUNX2, COL1A1 and Osterix as well as the alkaline phosphatase activity. Taken altogether, these results suggested that miR-130a and miR-27b could promote osteogenesis in human MSCs by targeting the PPARγ.